ASUHAN KEBIDANAN PADA WANITA USIA SUBUR DENGAN FLOUR ALBUS MELALUI PENERAPAN VULVA HYGIEN MENGGUNAKAN REBUSAN SIRIH MERAH - Helen Kristeti; Risqi Utami; T. Marzila Fahnawal; Maryana; Yenni Aryaneta (Universitas Batam, 2023)
Flour albus is a symptom that is often experienced by most women. Fluor albus that has an impact is pathological fluor albus which is caused by an infection in the vagina (fungi, bacteria, parasites, viruses) so it needs immediate treatment. Research on reproductive health shows that around 75% of women in the world will experience vaginal discharge at least once in their lifetime, and as many as 45% will experience 2 or more times. One of the plants that is often used as an alternative ingredient to cure leucorrhoea is betel leaf (Pipper bettle L.). Some of the ingredients in betel leaves in the form of essential oils contain phytochemical compounds such as tannins, essential oils, flavanoids, alkaloids and saponins which can inhibit the growth of pathogenic bacteria. The purpose of writing is to provide midwifery care, with midwifery care management in accordance with midwifery service standards. Midwifery care that is applied is vulva hygiene in women of childbearing age with flour albus. The type of research used in the preparation of practice reports is descriptive research using the case study method. Data collection methods are participatory observation, interviews, measurements, documentation. The research instrument is the format of midwifery care. Based on the results of midwifery care, it was found that the effectiveness of giving betel leaf decoction in treating leucorrhoea in fertile age women was very effective for non-pharmacological therapy for Flour Albus